Using Multi-Mission Satellite Elevation Data for Delineation of Gilgit Watershed in Pakistan in Geographical Information Technology Environment: Using Multi-Mission Satellite Elevation Data for Delineation of Gilgit Watershed in Pakistan in Geographical Information Technology Environment - Irfan, Muhammad; Shafiq, Muhammad; Khan, Mehrab (International Journal of Economic and Environmental Geology, 2024)
The hydro-climatological variations in Gilgit watershed of Upper Indus basin is less scientifically understood due to diverse geography, remoteness of the region and larger variations in climatic conditions. Extraction of catchments at multiple scales is an important task in undertaking the watershed management studies. Satellite remote sensing (SRS) and geographical information technology (GIT) provide a very useful method to study the watersheds. In view of the facts, watershed/ natural resources management in Gilgit river basin, application of geospatial techniques to various elevation datasets is required in order to obtain more accurate results using these elevation datasets. To achieve this goal, the topographic feature extraction has been studied in the catchment of Gilgit river using different Digital Elevation Models (DEMs) viz., SRTM, ASTER GDEM and GTOPO30. Several small watersheds for the Phakor, Karamber, East Gammu, Bhort and Bad-e-Swat glaciers were delineated for the basin definition. The delineated watersheds have been visually analyzed against the optical Landsat 8 OLI imagery for mountainous ridge matching. The results revealed that, SRTM 30m (radar based) exhibited more accuracy among these DEMs because of its precise delineation in the Gilgit sub-basin. However, it is appropriate to say that computed area from all three DEMs generally show close agreement. This study is a good contribution towards better understanding of the watershed management and the hydrological responses in Gilgit watershed of the upper Indus catchment.